Parental burnout: Effect of home quarantine during the COVID-19 Pandemic - Yoleri, Sibel (Southeast Asia Early Childhood Journal, 2022)
The coronavirus (Covid-19) disease has not only caused health or economic difficulties as an infectious disease but has led to great impacts on individual lives and families. Parenthood may be challenging during the Covid-19 because of short- or long-term home quarantine periods in many countries. This study was carried out to investigate the effect of the home quarantine and other variables (such as the number of children, time spent with children) on parental burnout in Turkish parents. A total of 251 parents, who had a child in the preschool period, were included in the study. Personal Information Form and Parental Burnout Inventory, developed by Roskam et al. (2018) of which Turkish validity and reliability studies were conducted by Arıkan et al. (2020), were used as data collection tools. Descriptive statistics (means, standard deviations, and percentages) were used to describe the demographic characteristics of the sample and study variables. And also computed one-way analysis of variance (ANOVA) to test mean differences for categorical variables (i.e., time spent with children, having a number of children) was conducted. This study concluded that the level of burnout increased in the parents with children in preschool in quarantine periods in terms of the number of children at home and the time spent with children. Significantly, burnout means scores of mothers and fathers are close to each other. On the other hand, the mean score of the burnout inventory “I have zero energy for looking after my child(ren) to the development of my child” was found to be high. This study showed that concern about COVID-19 predicted parental burnout. According to the study result, the experts should consider the possibility of parental burnout as they work with parents, and children, understanding that the long-time effects of the pandemic may extend beyond the period of the current period in place orders.